Stepwise Biogenesis of Subpopulations of Lipid Droplets in Nitrogen Starved Phaeodactylum tricornutum Cells - Jaussaud, Antoine; Lupette, Josselin; Salvaing, Juliette; Jouhet, Juliette; Bastien, Olivier; Gromova, Marina; Maréchal, Eric (Frontiers in Plant Science, 2020)
Diatoms are unicellular heterokonts, living in oceans and freshwaters, exposed to frequent environmental variations. They have a sophisticated membrane compartmentalization and are bounded by a siliceous cell-wall. Formation of lipid droplets (LDs), filled with triacylglycerol (TAG), is a common response to stress. The proteome of mature-LDs from Phaeodactylum tricornutum highlighted the lack of proteins involved in early-LD formation, TAG biosynthesis or LD-to-LD connections. These features suggest that cytosolic LDs might reach a size limit. We analyzed the dynamics of LD formation in P. tricornutum during seven days of nitrogen starvation, by monitoring TAG by mass spectrometry-based lipidomics, and LD radius using epifluorescence microscopy and pulse field gradient NMR (PFG-NMR). We confirmed that mature LDs reach a maximal size. Based on PFG-NMR, we did not detect any LD-LD fusion. Three LD subpopulations were produced, each with a different maximal size, larger-sized LDs (radius 0.675 ± 0.125 µm) being generated first. Mathematical modeling showed how smaller LDs are produced once larger LDs have reached their maximum radius. In a mutant line having larger cells, the maximal size of the first LD subpopulation was higher (0,941 ± 0,169 µm), while the principle of stepwise formation of distinct LD populations was maintained. Results suggest that LD size is determined by available cytosolic space and sensing of an optimal size reached in the previous LD subpopulation. Future perspectives include the unraveling of LD-size control mechanisms upon nitrogen shortage. This study also provides novel prospects for the optimization of oleaginous microalgae for biotechnological applications.